(1) Solution:-
45a4÷ 9a2
= 45a4/9a2
= 5a2
(2) Solution:-
-24a5÷ 3a2
= – 24a5/3a2
= -8a3
(3) Solution:-
30a4 x3 ÷ 6a2 x
= – 30a4 x3 / 6a2 x
= -5 a2 x2
(4) Solution:- – 28 x4 y3 z2 ÷ 4x y z
= – 28 x4 y3 z2 /4x y2 z
= – 7 x3 y z
(5) Solution:-
-36a3 z3 y2 ÷ (-4ayz)
= – 36a3 z3 y2/- 4ayz
= 9a2y z2
(6) Solution:-
– 22 x3 y2z÷ – 2xyz
= – 22 x3 y2 z/ – 2xy z
= 11 x2 y
(7) Solution:-
(3a3 b3– 2a2 b3) ÷ a2b2
= 3a3b2 – 2a2 b2 /a2 b2
= 3 a3 b2 /a2 b2 – 2a2 b3 /a2 b2
= 3a- 2b
(8) Solution:-
(36 x4 y3 + 9x5 y2) ÷ 9xy
= 36 x4 y3 /9 x y+ 9x5 y2 /9xy
= 4 x3 y2 + x4 y
(9) Solution:-
(a3 b4– 3a7 b7) ÷ – a3 b3
= a3 b4 / a3 b3 – 3a7 b7/ a3 b3
= b- 3a4 b4
(10) Solution:-
(6a b -9a b) V 3a b
= 6a b/3a b – 9a b/3a b
= 2a b- 3a b
(11) Solution:-
(15x3 y3 + 12x3 y2– 1 x5 y3 ) ÷ 3x2 y2
= 15x3 y3/ 3x2 y2 + 12x3 y2 / 3x2 y2 – 12x3 y2/ 3x2 y2
= 5xy+ 4x – 4x3 y
(12) Solution:-
(6x8 y6 z- 4x4 y3 z2 + 2x2y2z2) ÷ 2 x2 y2 z
= 6x8 y6 z/ 2 x2 y2 z – 4x4 y3 z2/ 2 x2 y2 z+2x2y2z2 /2 x2 y2 z
= 3 x6 y4 – 2 x2z + z
(13) Solution:-
(24a2 b2 c- 15a4 b4 c4 – 9a2 b6 c2) ÷ (-3ab2)
= 24a2 b2 c /-3ab2– 15a4 b4 c4 /-3ab2– 9a2 b6 c2/ -3ab2
= – 8a c + 5a3 b2 c4+ 3ab4 c2
(14) Solution:-
(a3 b3 + 2a2 b3) ÷ (a+2b)
= a3 b3/ a+2b + 2a2 b3/ a+2b
= a2 b2
(15) Solution:-
(6x2 +x-2) ÷ (2x -1)
= (6x2 +x-2)/(2x-1)
= 3x+2
No comments:
Post a Comment